C8 cross transfer for the treatment of caudal brachial plexus avulsion in three dogs. Issue 1 (January 2017) - Moissonnier, Pierre; Carozzo, Claude; Thibaut, Jean‐Laurent; Escriou, Catherine; Hidalgo, Antoine; Blot, Stéphane
Abstract: Objective: To evaluate the cervical nerve 8 cross‐transfer technique (C8CT) as a part of surgical treatment of caudal brachial plexus avulsion (BPA) in the dog. Study Design: Case series. Animals: Client‐owned dogs suspected to have caudal BPA based on neurological examination and electrophysiological testing ( n = 3). Methods: The distal stump of the surgically transected contralateral C8 ventral branch (donor) was bridged to the proximal stump of the avulsed C8 ventral branch (recipient) and secured with 9‐0 polypropylene suture under an operating microscope. A carpal panarthrodesis was performed on the injured limb after C8CT. Results: Surgical exploration confirmed avulsion of nerve roots C7, C8, and T1 in all cases. There was no evidence of an iatrogenic effect on the donor forelimb. Gradual improvement in function of the affected forelimb occurred in all dogs, with eventual recovery of voluntary elbow extension. Reinnervation was evident in EMG recordings 6 months postoperatively in all three dogs. Stimulation of the donor C8 ventral branch led to motor evoked potentials in the avulsed side triceps brachialis and radial carpus extensor muscles. Variable functional outcome was observed in the 3 dogs during clinical evaluation 3‐4 years after surgery. Digital abrasion wounds, distal interphalangeal infectious arthritis, and self‐mutilation necessitated distal phalanx amputation of digits 3 and 4 in 2 dogs. Conclusion: C8CT provided partial reconnection of the donor C8 ventral branch to the avulsed brachial plexus in the 3 dogs of this series. Reinnervation resulted in active elbow extension and promoted functional recovery in the affected limb.